Study on Microbial and Ecophysiological Indices of Tea Soils in Chattogram and Khagrachari Districts of Bangladesh - Akter, Sanjida; Das, Shuva; Roy, Sajal; Chowdhury, Nasrin (Chittagong University Journal of Biological Sciences, 2024)
The evaluation of soil microbial and ecophysiological properties is highly significant to maintain soil health and sustainable production of crops. Thus, this research was carried out to observe the status of different microbial and ecophysiological indices of tea soils belonging to Oodaleah tea garden (OTG) and Tin Tohori tea garden (TTTG) located in Chattogram and Khagrachari districts of Bangladesh. A total number of thirty seven and twenty four surface soil (0-9 cm) samples were collected from OTG and TTTG, respectively. The areas of both the tea gardens are mostly covered by low hill ranges to terraces. Irrespective of the sampling sites, the mean values of microbial biomass carbon (MBC), microbial activity (MA), substrate induced respiration (SIR), microbial quotient (qMic) and mineralization quotient (qM) were found to be 3.73%, 6.25%, 2.15%, 26.19% and 20.0% higher, while metabolic quotient (qCO2) was 7.69% lower in TTTG compared to OTG. The findings of this study clearly showed the highest microbial responses at toeslope except MA in TTTG. As for OTG, the MA and qM at toeslope significantly differed (p<0.05) from the values found at summit. However, all the microbial and ecophysiological indices did not differ significantly (p>0.05) among the three different slopes for TTTG. All the microbial indices were positively correlated, while a significant (p<0.01) negative correlation was found between MBC and qCO2 both for OTG and TTTG. Besides, the correlation between qCO2 and qMic was also found negative and significant (p<0.05) both for OTG and TTTG. Chittagong Univ. J. B. Sci. Vol. 12 (1 & 2): 45-55, 2024